INVESTMENT DECISION IN THE AGENCY THEORY FRAMEWORK - Ahmad Cahyo Nugroho; Muhammad Firdaus; Trias Andati; Tony Irawan (Universitas Mercu Buana, 2018)
Abstract. This studies aims to observe the development of literature on companyinvestment decisions and to decide what research should be conducted further oncompany investment decisions in the theoretical framework of agency theory. Themethods used were bibliometric network analysis and literature review. This study hasmapped out the literature on company investment decisions based on agency theory.This study shows that the topics on competition research, corporate governance, andcapital structure are closely related to the company investment decisions in the theory ofagency, and it is worth investigating. Therefore, it is necessary to develop furtherempirical research related to company investment decisions in the framework related toagency theory by analyzing the influences of competition, corporate governance, andcapital structure comprehensively on invesment decision.